Synthesis, Characterization, Molecular Docking, Acetylcholinesterase and α-Glycosidase Inhibition Profiles of Nitrogen-Based Novel Heterocyclic Compounds - Gülçin, İlhami; Petrova, Olga, V; Taslimi, Parham; Malysheva, Svetlana F.; Schmidt, Elena Yu; Sobenina, Lyubov N.; Gusarova, Nina K.; Taslimi, Parham (Wiley-V C H Verlag Gmbh, 2022)
In this study, a series of nitrogen-based novel heterocyclic compounds were synthesized and characterized by elemental analysis, IR and NMR spectra. The novel synthesized nitrogen-based novel heterocyclic compounds were evaluated against the acetylcholinesterase (AChE) and alpha-glycosidase enzymes. These compounds showed IC50 values in range of 0.76-28.04 mu M against AChE as a cholinergic enzyme, and 26.10-82.17 mu M against alpha-glycosidase as a hydrolytic enzyme. On the other hand, they demonstrated K(i )values between 1.25 +/- 0.22-25.36 +/- 4.72 mu M against AChE, and 25.07 +/- 4.57-78.55 +/- 17.04 mu M against alpha-glycosidase enzymes. The synthesized nitrogen-based novel heterocyclic compounds exhibited effective inhibition profiles against both indicated metabolic enzymes. These results may contribute to the development of new drugs particularly to treat some disorders, which widespread display in the world including Alzheimer's disease and diabetes. Furthermore, molecular docking calculations were made to compare the theoretical biological activities of nitrogen-based novel heterocyclic compounds against proteins including enzymes. After these calculations, ADME/T analysis was performed to examine the drug properties of nitrogen-based novel heterocyclic compounds.
Keywords: Acetylcholinesterase; Enzyme Inhibition; Alpha-Glycosidase; Heterocyclic Compounds; Molecular Docking